Psychological effects of the recitation of the Quran among university students through the investigation of heart rate variability and breathing behaviour - Nayef, Eman Ghanim (2019)
The Quran is the word of Allah revealed to the Prophet Muhammad and Quran recitation is a highly recognised among the Muslim community in their worships and prayer. One of the important effects of the Quran on undergraduate student learning and their achievement is reflected in emotions. Emotions control the attention of students, influence their motivation to learn, modify their choice of learning strategies and affect their self-regulation of learning. Furthermore, emotions are part of student identity, and they affect personality development, psychological health and physical health. This study involves analysing the psychological effects during reciting Quran for the undergraduate students. The objectives of this research are to examine the effects of Quran recitation on the Heart Rate Variability (HRV) and Breathing Behaviour (BB) among undergraduate university students, furthermore, the relationship between HRV/BB with different types of Quran recitation, also to discover the relationship of different verses and reading styles of reciting Quran with relaxation among students. Repeated measures quasi experimental design was conducted in this study. For HRV test, thirty undergraduate students whom participated in this test were divided into two groups; good Quran reciters group and weak Quran reciters group. The parameters of heart rate variability (HRV) are coherence ratio and accumulate coherence score, were measured to examine the outcome. And for breathing behaviour test, six undergraduate students all are good Quran reciters whom involved in this test, the parameter of BB breathing cycle (B/min) were measured to examine the outcome. Pre–post test score mean differences comparison showed significant differences in HRV, when all p-values < 0.05 for both group. And the results between good reciters group and weak reciters group also shows a clear significant difference in HRV data when all p-values < 0.05. Good reciters have effects on better HRV performance as compared to weak reciters. The Breathing Behaviour testing outcome based on Pre-Post-test illustrate that the p value <0.05 which show significant differences between the baseline and reciting Quran. According to the finding of this research, students who are good in reciting Quran, they have higher scores in heart rate variability depending on their higher scores in coherence ratio and accumulate coherence score of HRV. Also, reciting Quran with Tajweed rules specially Maad with long breathing, and Waqf with stop breathing, tends to more control on deep and slow breathing which reflect on relaxation conditions. Based on the result of the HRV and Breathing Behaviour through reciting Quran for students, results indicate high scores of HRV, and breathing cycle per minute indicate a low B/min, which means that the heart and breath work efficiently together, the parasympathetic branch of the ANS is activated, creating the relaxation response. This research concluded that the students who are good in reciting Quran, they have higher scores in heart rate variability and the breathing cycle become slower during reciting Quran, which mean the breath become a peace breath, that makes the students calm and relax.